Exercise joy, social support, practice commitment, and athletic efficacy in young basketball players - Setiawan, Agus; Rosidi, Sakban; Aswara, Agung Yuda (ARKA INSTITUTE, 2025)
This study aims to examine the influence of enjoyment in sports and social support on training commitment, as well as the direct and indirect effects of these two variables on athletic self-efficacy through training commitment in young basketball players. The method used in this study is quantitative research, which aims to test certain theories by analyzing the relationship between variables. This research is secondary and adopts the Internet Mediated Research (IMR) method through Google Form, which resulted in 413 research samples. The results of the study indicate that there is a direct effect of enjoyment in sports on social support in young basketball athletes. In addition, the results of the study also show direct and indirect effects of enjoyment in sports through social support on training commitment in young basketball athletes. Furthermore, this study revealed that there are direct and indirect effects of enjoyment in sports and social support on athletic self-efficacy through training commitment in young basketball players. The conclusion of this study is that enjoyment in sports and social support play an important role in increasing training commitment and athletic self-efficacy, which in turn can support the development of young basketball players.